Re-thinking power in student voice as games of truth: dealing/playing your hand. (3rd April 2017) - Nelson, Emily
Abstract: Theorising power in student voice is contested terrain dominated by critical theory but challenged increasingly by post-structural approaches. Although critical approaches have suited the advocacy needed to establish student voice as worthy social justice work in this article I explore post-structural resources that more generatively account for the complexity, multiplicity and ambiguity of power dynamics within student voice initiatives. I examine what is opened up when power is conceptualised as 'games of truth', multifarious, generative and deployed tactically by both students and researchers to co-produce 'truths' that emerge as student voice. I 'plug in' games of truth to data from one student voice encounter, researcher reflections and participatory research discourses to generate an assemblage of power dynamics in student voice differently. I argue that viewing power as games of truth opens up to student voice as contingent and recursive tactical contests over truth played between mutually powerful, yet differently powered players.